Penerapan Etika Bisnis Islam dalam Konteks Produsen dan Konsumen: Ke Arah Tanggung Jawab Sosial Perusahaan - Muhammad Anas (Millah: Journal of Religious Studies, 2008)
In fact, business activity neglecting ethics harms consumers and employees as many cases occurred in this country i.e. formalin case, little wage, oil stealing in Kalimantan, industrial cesspool, transaction of stolen wood, etc. Such facts and cases, to ethical perspective, are due to separation between ethics and business which has a negative impact on human lives. But, ethics and business are two entities being able to be united as one. According to Islam, business is not only an activity to get financial profit, but also the activity to attain essence of humanity as implementation of which becomes human responsibility as creature and caliph in achieving Allah's favor. Therefore, Islam teaches values of business practice such as unity, freedom, responsibility, equality, virtue, and honesty. It is an valuable teaching that all parties like producer, consumer, employer, employee, and society must apply business ethics, because this does not deal with vertically producer's responsibility only, but also with existence of business activity its self. Summarily, mutual and harmonious relationship among involved parties in business activity will be constructed, if values of business ethics are held as fundamental source for their business practice.  Keyword: ethics, business, human responsibility.